Editorial Foreword - Ab Gani, Muhamad Abdul Aziz; Ramli, Ishak; Yahaya, Mohamad Hafiz; Taharuddin, Nurul Shima; Md Nazri, Haslinda; Rosman, Muhammad Redza; Nazrin, Nizar (Idealogy Journal; Vol 4 No 1 (2019): Idealogy Journal (April 2019), 2021)
No Abtsract